Studies on the Removal of Sulfides from Wastewater - Ahmad, Naveed (2009)
In the present work a thorough and systematic study has been made on the removal of sulfides by oxidation and precipitation methods. Both synthetically prepared sulfide solution and industrial waste water sample containing sulfide were treated by this method in the present investigations. Iodometric and spectrophotometeric methods were used for the analysis of sulfide and sulfur bearing other radicals. The treatment was carried out by aeration in the presence of UV light, oxidation by hydrogen peroxide in the presence of ferric oxide catalyst, precipitation using iron salts followed by aeration and aeration in the presence of ultrasonic vibration. Aeration in the presence of UV light was found to be very effective for the removal of sulfide. The effects of sulfide concentration and partial pressure of oxygen on the kinetics of oxidation of sulfide under specific UV light intensity was investigated. Sulfide oxidation was found to be faster at higher UV light intensity. The catalyst synthesized for the oxidation of sulfide was analyzed by XRD, FT-IR, SEM and EDX. The precipitate formed in the treatment process was also analyzed following the above mentioned techniques. SEM analysis of ferric oxide synthesized by sol-gel technique revealed that the average particle size of the sample was less than 200nm. The XRD picture of the catalyst reveals that the presence of non-stiochiometric ferric oxide appears as a major crystalline phase. In the FT-IR spectra of the catalyst sample stretching vibration of FE-O was observed in different regions. Oxidation of sulfide by hydrogen peroxide in the presence of synthesized ferric oxide catalyst was also found to be very effective. The effects of sulfide concentration, catalyst loading, hydrogen peroxide dosing and temperature were investigated on the kinetics of sulfide oxidation. Sulfide oxidation by hydrogen peroxide in the presence of catalyst was found to be faster with the increase in temperature. Before oxidation initially the sulfide solution was highly alkaline (pH =11-12) and during oxidation the solution became almost neutral (pH=7-8). It was observed that by precipitation more than 70% of sulfide was removed from the wastewater. Complete removal of sulfide was achieved by aeration in the presence of precipitate formed. From the SEM picture of the precipitate formed no distinct or definite size of the particle was observed. Average particle size of the precipitate was found to be 500nm. From the EDX analysis of the precipitate, it was confirmed that Fe and S were the major elements present in the sample. Some amount of Na and Cl were also observed in the sample. Aeration in the presence of ultrasonic vibration has also been carried out for the removal of sulfide. The effects of air flow rate and sulfide concentration were investigated on the kinetics of sulfide oxidation. Oxidation was carried out at different ultrasonic vibration frequencies. Rate of sulfide oxidation was found faster at higher air flow rate and sulfide concentration. The results of this study are expected to be useful for the assessment of different alternatives for the removal of sulfide as well as for actual remediation of sulfidic wastewater in chemical and allied industries.